ANALISIS PELAKSANAAN PENEMPATAN KARYAWAN DEPARTEMEN FOOD & BEVERAGE DI HOTEL MUTIARA MERDEKA PEKANBARU - Artman "; Meyzi Herianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted at the Department of Food & Beverage at Hotel Mutiara Merdeka Pekanbaru. This is because this company is one of the service companies are quite well known and has been standing long enough dipekanbaru.The purpose of this study is to investigate or analyze the placement of employees in the Department of Food & Beverage at Hotel Mutiara Merdeka Pekanbaru. The research methods include the location of the research conducted at the Department of Food & Beverage at Hotel Mutiara Merdeka Pekanbaru, types and sources of data used are primary data and secondary data.Factors employment of employees at the Department of Food & Beverage at Hotel Mutiara Merdeka Pekanbaru seen from indicators of academic achievement, experience, physical and mental health, age. From the results of respondents to the indicators of staffing factors Ministry of Food & Beverage at Hotel Mutiara Merdeka Pekanbaru is right.From the research leader of the company should be able to adjust the positions of employees with employee education, and leadership should be more involved in the process of employment of employees in the Department of Food & Beverage at Hotel Mutiara Merdeka Pekanbaru.Keywords: Implementation, Placement, Employee